Pengaruh Ephemeral Content dan E-WOM terhadap Purchase Intention Millenial Customers pada UMKM Industri Kuliner di Surabaya - Mettan, Santho Vlennery; Sancoko, Aldo Hardi (Jurnal Keuangan dan Bisnis, 2021)
Indonesian’s Millennials are estimated to reach 70% of the productive population in 2020-2030 (BPS 2018), who cannot be separated from the internet and social media (Harahap 2017). Due to this fact, (Hsu 2018) and (Benini 2018) claim that millennials are afraid of being left behind by ephemeral content which will disappear within 24 hours so that many social media platforms are equipped with these temporary content features and companies are using temporary content strategies to reach more consumers. SMEs on the other hand have low knowledge of ephemeral content, even though 84% of millennials buy products due to the influence of social media, where ephemeral content lies within (Boen 2016). In the other hand, word-of-mouth has a significant impact on customer purchasing decisions until now. Along with the change to the digital era, word-of-mouth is being accelerated with the help of the internet, it called e-WOM, where many businesses use social media or other online platforms to promote business. The results showed that the two variables of ephemeral content and word-of-mouth with the help of the internet had a significant effect on customer purchase intentions, especially the millennial customer for SMEs in Surabaya City. In the future, by implementing ephemeral content in SMEs media social will increases their customer’s e-WOM.